Development of a flexible customised compression garment pattern design system - Salleh, Mohamed Najib; Mad Lazim, Halim; Othman, Siti Norezam; Merican, Amir Feisal (Inderscience, 2013)
The paper investigated a new method that can be used to develop a 3D customized compression garment model for athlete.The developed system is able to design the compression garment based on the athlete body data, type of fabric and pressure for their top performance.The outcome of the research is a system that not only can design a customized compression garment, but also flexible enough to be used to create a variety of compression garment that can exert different pressure.